Identity in African literature : a study of selected novels by Ngungi Wa Thiong'o - Mogoboya, Mphoto Johannes (My University, 2004)
Refer to document
Thesis (M. A. (English Studies)) -- University of Limpopo, 2004
Keywords: African literature; Identity; African writers; Wa Thiong'o Ngungi; African literature (English) -- History and criticism; Literature -- History and criticism; English literature -- Black authors -- History and criticism